Phosphorylation regulates cullin-based ubiquitination in tumorigenesis - Yifan Chen; Xuejing Shao; Ji Cao; Hong Zhu; Bo Yang; Qiaojun He; Meidan Ying (Elsevier, 2021)
Cullin-RING ligases (CRLs) recognize and interact with substrates for ubiquitination and degradation, and can be targeted for disease treatment when the abnormal expression of substrates involves pathologic processes. Phosphorylation, either of substrates or receptors of CRLs, can alter their interaction. Phosphorylation-dependent ubiquitination and proteasome degradation influence various cellular processes and can contribute to the occurrence of various diseases, most often tumorigenesis. These processes have the potential to be used for tumor intervention through the regulation of the activities of related kinases, along with the regulation of the stability of specific oncoproteins and tumor suppressors. This review describes the mechanisms and biological functions of crosstalk between phosphorylation and ubiquitination, and most importantly its influence on tumorigenesis, to provide new directions and strategies for tumor therapy.